2021
DOI: 10.32473/edis-in1266-2019
|View full text |Cite
|
Sign up to set email alerts
|

Mottled Water Hyacinth Weevil Neochetina eichhorniae Warner (Insecta: Coleoptera: Curculionidae)

Abstract: Sometimes referred to as the ‘mottled water hyacinth weevil’, Neochetina eichhorniae Warner is a weevil that attacks the invasive, aquatic plant, water hyacinth, Eichhornia crassipes (Mart.) Solms. Water hyacinth is considered one of the most destructive plants in aquatic ecosystems in the United States and, as a result, is listed in both the federal noxious weed list and Florida’s list of prohibited aquatic plants. Neochetina eichhorniae is host specific and causes substantial damage to water hyacinth, making… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
(32 reference statements)
1
1
0
Order By: Relevance
“…The mean leaf loss of the E. crassipes increased with increasing water nutrient concentrations and decreased with a decrease in the weevil density (Figure 7A, B, and C). Similar to the current study, other studies reported that the E. crassipes leaf damage and loss were high as the density of N. bruchi and N. eichhorniae increased (Kariuki and Minteer, 2021), but E. crassipes productivity increased with a decrease in the feeding intensity of the herbivores when they were at a lower density (Bownes et al, 2010). The results imply that the biocontrol of E. crassipes is influenced by both herbivore densities and water nutrient levels.…”
Section: Effect Of Water Nutrient Levels Neochetina Bruchi and Neoche...supporting
confidence: 88%
See 1 more Smart Citation
“…The mean leaf loss of the E. crassipes increased with increasing water nutrient concentrations and decreased with a decrease in the weevil density (Figure 7A, B, and C). Similar to the current study, other studies reported that the E. crassipes leaf damage and loss were high as the density of N. bruchi and N. eichhorniae increased (Kariuki and Minteer, 2021), but E. crassipes productivity increased with a decrease in the feeding intensity of the herbivores when they were at a lower density (Bownes et al, 2010). The results imply that the biocontrol of E. crassipes is influenced by both herbivore densities and water nutrient levels.…”
Section: Effect Of Water Nutrient Levels Neochetina Bruchi and Neoche...supporting
confidence: 88%
“…Eichhornia crassipes plants in experimental buckets had a high adult density of N. bruchi and N. eichhorniae when they were treated with a high density of the weevils. The highest mean number (43) was obtained using a high adult density of weevils on E. crassipes plants that received the highest nutrient level (Table 2), which was substantially different from the lowest result. In a combined application of the weevil with white amur, Delfosse et al (1976) found a maximum of 89.4 N. eichhorniae per 388 E. crassipes plants in a pool per season, which is lower than the current result.…”
Section: Effect Of Nutrient Levels Neochetina Bruchi and Neochetina E...mentioning
confidence: 67%